Nasopharyngeal carcinoma with mastoid recurrence after concurrent chemoradiotherapy masquerading as acute otomastoiditis. Issue 6 (December 2017) - Hu, Chih-Yu; Huang, Shiang-Fu; Ho, Wan-Ling; Chuang, Wen-Yu; Chan, Kai-Chieh
Abstract: Nasopharyngeal cancer (NPC) with mastoid recurrence is extraordinarily rare, and its development is thought to involve the Eustachian tube. We herein report a case of NPC with mastoid recurrence masquerading as acute otomastoiditis with facial paralysis in a 60-year-old man 44 months after concurrent chemoradiotherapy. The diagnosis was confirmed by exploratory tympanomastoidectomy with biopsy and Epstein–Barr-encoding region (EBER) in situ hybridization. Distant liver metastasis was detected simultaneously, and the patient underwent salvage treatment. He died 15 months later. Despite the rarity of mastoid recurrence, clinicians should be vigilant in the differential diagnosis of mastoiditis in patients with NPC after radiotherapy. Tumor biopsy and EBER in situ hybridization can aid in the accurate diagnosis of this uncommon condition.